ANALISIS KINERJA ORGANISASI PADA KANTOR KECAMATAN BLORA - Pria Bintang Aditama; Nina Widowati (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2017)
In the era of regional autonomy and decentralized, the performance of public organizations have an important role in providing public services to the community. Blora subdistrict is a public organization that is in the province of Central Java. Blora subdistrict has a duty to carry out the wheels of government and public services at the district level. In achieving these goals is certainly influenced by the performance of the organization as a whole. As a district located in the city, it would be a representation of other subdistricts be interested researchers to discuss it. The purposed of this research is to analyze the performance of Blora District organizational in achieving their objectives, accordimg to the vision and mission of the organization. To see the performance of the organization, researchers viewed from various aspects, such as productivity, responsiveness, quality of service, cooperation, use of resources and timeliness. The second objective was to describe the factors inhibiting the Blora District of organizational performance. This research used qualitative descriptive study that refers to the concept of performance indicators and the condition of the locus recently. Based on the results, it can be explained that the performance of the organization has been run well. Such as the responsiveness indicators, quality of service, cooperation and timeliness. But, there’s a problem with the human resources and infrastructure. Therefore, the researchers gave suggestions to increase the competence of human resources. The organization have to optimizing existing facilities and infrastructure to support the activities and increase budget allocations and adjust according to budget targets.